STUDENTS’ PERCEPTIONS TOWARDS THE ADOPTION OF ODT AND PBL IN SPEAKING CLASS - Budiarto Budiarto; Suhendar Suhendar; Sri arfani (STIBA IEC JAKARTA, 2022)
There are many researchers who have been discussing EFL learners’ perceptions on the implementation of online digital technology (ODT), but there are few of them who specifically investigate their familiarity in using technology when applying project-based approach. This research analysis students’ attitudes in using ODT to improve their speaking skills and how familiar students use ODT to accomplish a project in a Speaking Class. Because the approach of learning English in this research is PBL with ODT, the students must be familiar with the technology in order to create some projects assigned. Therefore, they had to own smartphones or laptops, and familiar with very basic ODT before beginning the program. 24 students of Speaking class were selected and trained to pedagogically show their awareness towards the learning approach and the use of ODT. The researcher divided them into some smaller groups to work together to improve their projects by looking at their learning approach with technology. The result of the posttest indicated their positive attitudes towards the implementation of PBL in the Speaking class with digital technology and the increasing familiarity of using ODT. They realized that they needed to create, and evaluate the results of their project by themselves during online learning to improve their speaking skills. Keywords: Speaking, Project-based, ODT, Students’ Perceptions